The Adaptive Management System for the Tasmanian Wilderness World Heritage Area — Linking Management Planning with Effectiveness Evaluation - Jones, Glenys (Adaptive Environmental Management, 2009)
This paper provides a 30 year retrospective on the development of the adaptive management system for the Tasmanian Wilderness World Heritage Area (Australia). It describes the historical background, key influences and stages that paved the way to establishment of adaptive management. It outlines how effectiveness monitoring, evaluation and reporting are integrated with the management plan for the Area to establish an ongoing adaptive management cycle. The chapter presents figures and tools for adaptive management, including 5 useful questions for guiding the integration of effectiveness monitoring, evaluation and reporting into management plans and programs. Strengths and weaknesses of the adaptive management system are discussed. Key lessons and insights distilled from this experience are offered, including the importance of planned monitoring of management effectiveness; the role of stakeholder assessments; and the factors that can assist in sustaining longterm strategic programs despite ongoing institutional change. The chapter concludes with suggestions for fostering an enabling environment for adaptive management.
Keywords: Adaptive Management; Management Intent; Reserve Management; World Heritage

Appropriate ICT as a Tool to Increase Effectiveness in ICT4D: Theoretical considerations and illustrating cases - Reijswoud, Victor van (The Electronic Journal of Information Systems in Developing Countries, 2009)
The need to bridge the digital divide is no longer a point of discussion and therefore focus has shifted to the design and implementation of programs that have the potential to close the information and knowledge gap between the developing and developed nations. Unfortunately, the majority of these programs are small and mimic what has been successful in the developed world. It has become increasingly clear that these successes do not necessarily translate well in the context of developing nations. This paper develops the hypothesis that Information and Communication Technology (ICT) projects in developing countries will become successful only when they are adapted to local conditions. The general concept of Appropriate Technology (AT) will be explored for the field of ICT. AT has already been embraced by fields like architecture, building technology and agriculture, but has not yet been rooted in ICT. The paper proposes a preliminary theory of Appropriate ICT along the lines of existing theories in AT and System development. The theory identifies Appropriate Technology principles at three levels: hardware, software and ICT change management. By means of real life mini cases in the ICT for Development context in Africa, the guiding principles for Appropriate ICT are illustrated. The paper will conclude with an agenda for further research in the three identified levels. The research agenda targets academia, governments, NGO's and industry.
Keywords: IMPORTANT